Study Multiculturalism Based on The Koran - Nurjannah Nurjannah; Taklimudin Taklimudin; Busra Febriyarni (Institut Agama Islam Negeri (IAIN) Curup, 2023)
Multiculturalism is an understanding of differences, tolerance, mutual respect, and respect between human beings. Islam is a religion of Rahmatan Lil-Alamin throughout human life and the Qur’an is a guide for Muslims in it contains multicultural values. The importance of multicultural education is expected to be a solution to the reality of a diverse society both in terms of religion and culture as a potential development process that can appreciate the plurality and heterogeneity of religion, language, and culture. Philosophically, this multiculturalism departs from the assumption of human dignity and honor. And this principle is found in all the world's major religions. Because humans have a noble position, the rights attached to them must be respected and protected. The desecration and violation of these human rights are the suppression of universal humanity. To that end, there are several ways proposed by the Qur'an to respect differences and avoid conflict in a multicultural society. This paper aims to reveal the solution efforts of the Qur'an in realizing harmony in a multicultural society so that prolonged social friction does not arise.